2017
DOI: 10.1016/j.ejso.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of palliative resection of the primary tumour in advanced pancreatic and small intestinal neuroendocrine tumours: A systematic review and meta-analysis

Abstract: Meta-analysis demonstrates that palliative resection of primary SI-NETs and P-NETs in the setting of unresectable metastatic disease can increase survival. Although these results should be interpreted with caution due to potential selection and publication bias, the data supports consideration of surgery, particularly in patients with low tumour burdens and good functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 32 publications
2
41
0
1
Order By: Relevance
“…NCCN guidelines recommend the resection of the primary SBNET even in the setting of metastatic disease, thereby reducing the risk of obstruction or ischemia from the tumor or mesenteric adenopathy. In addition, resection of just the primary SBNET with no operative intervention of the liver metastases has been shown to be an independent predictor of survival, with significantly improved survival compared with those with no resection (NR) at all . Another option is tumor debulking where there is no curative intent, but surgical resection is performed to remove as much gross tumor as is safely possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCCN guidelines recommend the resection of the primary SBNET even in the setting of metastatic disease, thereby reducing the risk of obstruction or ischemia from the tumor or mesenteric adenopathy. In addition, resection of just the primary SBNET with no operative intervention of the liver metastases has been shown to be an independent predictor of survival, with significantly improved survival compared with those with no resection (NR) at all . Another option is tumor debulking where there is no curative intent, but surgical resection is performed to remove as much gross tumor as is safely possible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, resection of just the primary SBNET with no operative intervention of the liver metastases has been shown to be an independent predictor of survival, with significantly improved survival compared with those with no resection (NR) at all. 12,13 Another option is tumor debulking where there is no curative intent, but surgical resection is performed to remove as much gross tumor as is safely possible. A recent study by Ejaz et.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenteric desmoplasia/mass causes abdominal pain and small bowel obstruction due to the kinking of the small bowel and mesenteric ischemia, which severely impairs the quality of life . Resection of the primary tumor, regional lymph nodes, and the mesenteric mass is recommended to manage such symptoms and for the possible prognostic benefit even in the setting of unresectable distant metastases . The latest American Joint Committee on Cancer (AJCC) TNM staging for NETs of the jejunum and ileum (8th edition) defined a new category of N2 as a large mesenteric mass (LMM) >2 cm, 12 or more positive nodes, or involving the main superior mesenteric vessels .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Resection of the primary tumor, regional lymph nodes, and the mesenteric mass is recommended to manage such symptoms and for the possible prognostic benefit even in the setting of unresectable distant metastases. 11,[14][15][16][17][18][19] The latest American Joint Committee on Cancer (AJCC) TNM staging for NETs of the jejunum and ileum (8th edition) defined a new category of N2 as a large mesenteric mass (LMM) >2 cm, 12 or more positive nodes, or involving the main superior mesenteric vessels. 20 While liver metastasis is a well-established prognostic factor, the prognostic significance of LMM is ill-defined.…”
mentioning
confidence: 99%
“…Dissection of at least eight (10,14,20) or 12 (23) lymph nodes has a positive impact on survival. A recent metaanalysis showed that among patients with metastatic disease, palliative resection of the primary tumor conferred a survival benefit (24).…”
Section: Locoregional Enterectomy With Lymph Node Dissectionmentioning
confidence: 99%